Post MH370 mysterious disappearance: presumption of death in estate administration of a missing person - Mohd Noor , Nor Azlina; Halim, Akmal Hidayah (2015)
After 327 days since Malaysia Airlines Flight 370 disappearance, Malaysian government on 28 January 2015 has officially declared the loss of MH370 during a flight from Kuala Lumpur to Beijing as an accident and all of its 239 passengers and crew were ‘presumed dead’. The declaration is made in accordance with the Standards of Annexes 12 and 13 to the Chicago Convention on International Civil Aviation. Therefore this paper aims to examine the regulation relating to presumption of death and its effect to the estate administration of missing person. The discussion will deliberate the issue of whether the official declaration made by the government is a conclusive evidence for the estate beneficiaries to apply for grant of probate or letter of administration from the respective administrative bodies. The position in United States and United Kingdom will also be analyzed. The study adopts the doctrinal analysis by examining the existing primary and secondary materials including statutory provisions as provided in the Probate and Administration Act 1959 (Act 97), Rules of Court 2012, Evidence Act 1950 (Act 56) , Syariah Court Evidence (Federal Territories) Act 1997, case law and other legal and non-legal literatures. The paper concludes that the official declaration made by the government provides only room for the family members to apply for a declaratory order of presumption of death from the High Court before they can have the locus standi to deal with the estate administration process. It is also conclude that the current law regarding presumption of death is not sufficient and cannot be regarded as formulative of satisfactory guiding lines in administrating estate of missing person.